2017
DOI: 10.21833/ijaas.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle type effects on the scratch resistance of polyethylene-based nanocomposites

Abstract: The purpose of this paper is to investigate the effect of nanoparticle type on the scratch resistance of polyethylene-based nanocomposites at two ambient temperatures and various scratch velocities. An in-house pre-mix procedure is used to enhance the scratch resistance of polyethylene blend by the addition of three different types of nanoparticles, which are compatible with the host matrix. The results showed a good dispersion of nanoparticles into the host material matrix. The scratch resistance of polyethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…%) were observed, with no large aggregates of nanoparticles. Further evidence of the good dispersion of CNT and CB nanoparticle was obtained by using the TEM, which showed the presence of CB and CNT in the polymer matrix (Alghamdi, 2017;2019). Fig.…”
Section: Nanoparticle Dispersionmentioning
confidence: 83%
“…%) were observed, with no large aggregates of nanoparticles. Further evidence of the good dispersion of CNT and CB nanoparticle was obtained by using the TEM, which showed the presence of CB and CNT in the polymer matrix (Alghamdi, 2017;2019). Fig.…”
Section: Nanoparticle Dispersionmentioning
confidence: 83%
“…It was found that the incorporation of various nanofillers can lead to a significant improvement in the polyethylene composite properties which can be used in many applications such as packaging, electrical and thermal energy storage, automotive, and biomedical [1][2][3][4][5][6]. Recently, new polyethylene nanocomposites have been developed with the use of various processing methods, different types, and amounts of reinforcements [7][8][9][10][11][12][13][14][15][16]. These nanocomposites can be a cost-effective alternative to the high cost advanced composites and can be widely used in various industrial applications [1].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have focussed on the synthesis of new nanocomposites, starting from careful material selection and process control either by the direct use of an existing technique or by modified and adapted techniques. Various types of nanofillers have been used in polymer-based nanocomposite fabrication, such as exfoliated clay, modified carbon nanotubes and graphene [6][7][8][9][10][11][12][13][14][15]. However, achieving the uniform dispersion of the nanofillers is still an important scientific and technological challenge in nanocomposite fabrication.…”
Section: Introductionmentioning
confidence: 99%